Dexamethasone in bronchiolitis - منصور لينا (Latakia University Journal -Medical Sciences Series, 2021)
Aims of study: To determine the role of dexamethasone in the treatment of infant who are less than 2 years , and have the first episode of bronchiolitis Materials and Methods: infant who had been admitted to the hospital for an initial episode of wheezing ( 206 infants between 3 month and 2 years) , we randomly divided in two groups: Group (1): who they have been treated by dexamethasone ( intra-venous ) (1mg/kg/day) with bronchodilators ( inhaled ventolin) (0.03mg /kg in 3ml of normal saline ). Group (2): who they had been treated with only inhaled ventolin (0.03mg/kg in 3ml of normal salin) . We assessed the respiratory disease and the response to the treatment in two groups every 12 hours with : the rate of respiratory , severity of accessory muscle use and wheezing score and pulse oximetry in room air.and resumption of normal feeding , for 4 days . we used ( RDAI) Respiratory disease assessment instrument and ( RACS) Respiratory assessment change score , in assessment the infant . We excluded infants who were younger than 3 month , who required admission to the intensive care unit, or who had a history of congenital heart disease , mechanical ventilation . We used a proportional hazards model for our survival analysis . and square kai test . Results : 206 infants admitted with episode of bronchiolitis , the rate of response to intravenous dexamethasone and inhaled ventolin (103 infants) was obviously higher when was comparaed with the rate of response to the inhaled ventolin only ( 87,37% vs 13.6% ) . The duration of hospilatation with the infants who were treated with dexamethasone and ventolin was shorter than the infants who were treated with ventolin only , it was (3-5 ) days (81.55%) in group (1) vs (5-7) days (47.57%) in group (2) . Conclusions: There were differences between the infants who were treated with dexamethasone and ventolin and who treated with ventolin only , the use of dexamethasone (iv) accelerate the response to the treatment and reduce the duration of hospitalization in infants who have bronchiolitis .